1991
DOI: 10.1104/pp.96.3.794
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Cell and Tissue Water Relations Parameters in Storage Parenchyma of Sugarcane

Abstract: The osmotic pressure of the cell sap of stalk storage parenchyma of sugarcane (Saccharum spp. hybrids) increases by an order of magnitude during ontogeny to reach molar concentrations of sucrose at maturity. Stalk parenchyma cells must either experience very high turgor at maturation or have an ability to regulate turgor. We tested this hypothesis by using pressure probe techniques to quantify parameters of cell and tissue water relations of sugarcane storage parenchyma during ontogeny. The largest development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
57
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 20 publications
5
57
1
1
Order By: Relevance
“…stem cells: (1) the most commonly used pressure relaxation (PR) method, in which cell turgor pressure (P cell ) changes during the measurement, and (2) the more technically demanding pressure clamp (PC) method, in which P cell is maintained constant. Consistent with other studies in higher plant cells, Moore and Cosgrove (1991) Cosgrove and Steudle (1981) reported that a substantial (6-fold) and rapid (within 20 s) reduction in L p could occur in the same cell, and in hindsight, this presumably reflected the influence of aquaporins. Cosgrove and Steudle (1981) did not consider the lower L p as indicative of the L p in situ, and Wan et al (2004) reported that a reduction in L p was associated with perturbations to P cell on the order of 0.1 MPa.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…stem cells: (1) the most commonly used pressure relaxation (PR) method, in which cell turgor pressure (P cell ) changes during the measurement, and (2) the more technically demanding pressure clamp (PC) method, in which P cell is maintained constant. Consistent with other studies in higher plant cells, Moore and Cosgrove (1991) Cosgrove and Steudle (1981) reported that a substantial (6-fold) and rapid (within 20 s) reduction in L p could occur in the same cell, and in hindsight, this presumably reflected the influence of aquaporins. Cosgrove and Steudle (1981) did not consider the lower L p as indicative of the L p in situ, and Wan et al (2004) reported that a reduction in L p was associated with perturbations to P cell on the order of 0.1 MPa.…”
supporting
confidence: 76%
“…A similar degree of L p polarity, in the same direction, has been reported for stem parenchyma in Saccharum species (Moore and Cosgrove, 1991), although in their case L p OUT /L p IN was greater for PR (1.65) than for PC (1.16) methods, and we found the opposite (1.11 for PR and 1.27 for PC methods). Moore and Cosgrove (1991) suggested that the greater polarity found for the PR method may have been due to the fact that this method imposed larger changes in P cell than the PC method, but in our case, the P cell changes for both methods were small and similar (Fig.…”
contrasting
confidence: 41%
See 3 more Smart Citations